Special effects cinematography - Oxford Scientific Films; Image Quest (North Ryde, NSW. : Australian Film Television & Radio School, 1986)
The program illustrate how some of the effects of internal space are achieved and describes innovations in wildlife photography
Copy available in DVD format
Keywords: Cinematography -- Special effects; Trick cinematography; Trick films